THE SPEECH PROCESS AND ITS NOMINATIVE ASPECTS - Mardonovna, Suleymanova Nargiza (FKIP Unismuh Makassar, 2024)
This article investigates with linguistic aspects of speech process and its nominative aspects, including all units of language and speech while taking into consideration of intersections. As their number of unlike viewpoints, the syntax of external speech is diverse from internal speech syntax, because the internal speech is for the speaker and external one is pointed at someone. Final outcomes and shortcoming of the research may lead to better investigation as whole.